BEA WebLogic Server™ Administration Kit - Hawkins, Scott (Pearson, 2003)
The definitive guide to administering WebLogic Server 7! Maximizing performance, reliability, and efficiency Covers architecture, domains, clustering, JDBC, JMS, monitoring, and much more Includes 90-day trial version of WebLogic Server 7 WebLogic Server 7 administration complete: Maximizing efficiency, reliability, and performance. BEA WebLogic Server Administration Kit is the definitive guide to administering BEA WebLogic Server 7! Scott Hawkins starts where the documentation leaves off, illuminating crucial concepts and offering practical guidance for maximizing the performance, reliability, and efficiency of any WebLogic Server system. Unlike previous books on BEA WebLogic Server, this book is 100% focused on administration-and it presents essential techniques you simply won't find anywhere else. Coverage includes: Installing, starting, and stopping WebLogic Servers Defining effective Web Logic Server architectures Establishing and managing WebLogic Server domains Managing HTTP services Creating and working with WebLogic Server clusters Configuring and managing JDBC and JMS In-depth coverage of monitoring and performance tuning CD-ROM INCLUDED The accompanying CD-ROM contains a 90-day trial version of BEA WebLogic Server 7.0, the latest version of BEA's award-winning Java application server for developing, deploying, and managing Web applications with maximum scalability, performance, and fault tolerance.